Social values and the interpretation of Psalm 123 - Botha, Phil J. (Old Testament Essays, 2001)
It is contended in this article that Biblical texts can no longer be interpreted without taking cognisance of the contribution that the social sciences can make to the process of interpretation. Psalm 123 is analysed stichometrically and its poetic features are descriptionbed. The most important social values that are reflected in the psalm are then discussed in order to determine what contribution its cultural context can make to the process of interpretation. It is concluded that the real issue of the psalm is to have the honour of Yahweh restored and that this can only be recognised if its cultural context and its social values are understood.
free
Keywords: Christianity; Psalm 123; Social values